2016
DOI: 10.1039/c6dt03129c
|View full text |Cite
|
Sign up to set email alerts
|

An ethylene glycol intercalated monometallic layered double hydroxide based on iron as an efficient bifunctional catalyst

Abstract: Given the fact that the literature describing the intercalation of organic molecules in monometallic LDH systems is scarce, the present investigation is aimed at the generation of ethylene glycol intercalated Fe-Fe LDH with the objective of enhancing the surface area for further catalytic applications of industrially important and environmentally harmful organics. The solvothermal reaction of FeCl with urea in an ethylene glycol medium yielded a brown colored powder which was characterized employing a wide ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 60 publications
(81 reference statements)
1
7
0
Order By: Relevance
“…Moreover, peaks at 711.35 (Fe 2p 3/2 ) and 724.57 eV (Fe 2p 1/2 ) are in well accordance with trivalent state of iron, affirming the successful decoration of Fe 3 O 4 NPs on HNTs surface. 61,62 Besides, the core level spectrum of Co 2p exhibits binding energy peaks at 780.79 eV and 786.87 eV which matches well with the Co 2p 3/2 , while peak at 796.53 eV and 802.94 eV are correspondingly attributed to Co2p 1/2 , that confirms the existence of +2 oxidation state of cobalt in Co(II)@2-BPy@APTES@MHNTs. 63,64 Compositional analysis EDS and ED-XRF are the powerful tools that provides the information related to the elemental composition of discrete elements present in synthesized nanocomposites.…”
Section: Xpssupporting
confidence: 62%
“…Moreover, peaks at 711.35 (Fe 2p 3/2 ) and 724.57 eV (Fe 2p 1/2 ) are in well accordance with trivalent state of iron, affirming the successful decoration of Fe 3 O 4 NPs on HNTs surface. 61,62 Besides, the core level spectrum of Co 2p exhibits binding energy peaks at 780.79 eV and 786.87 eV which matches well with the Co 2p 3/2 , while peak at 796.53 eV and 802.94 eV are correspondingly attributed to Co2p 1/2 , that confirms the existence of +2 oxidation state of cobalt in Co(II)@2-BPy@APTES@MHNTs. 63,64 Compositional analysis EDS and ED-XRF are the powerful tools that provides the information related to the elemental composition of discrete elements present in synthesized nanocomposites.…”
Section: Xpssupporting
confidence: 62%
“…While a major thrust has been centered on the use of fluorite-structured oxides as oxidation catalyst, their capability to promote reduction reactions, preferably organic substrates, has not yet been explored extensively. ,, The production of nitroaromatics in pharmaceutical industries has been known to be a major threat to environment, and conversion of nitroaromatics to harmless chemicals could address the environmental concerns as well as add value to the economy. For example, aminophenols have been extensively used in analgesic and antipyretic drugs as well as photographic developer, corrosion inhibitor, anticorrosion lubricant, etc. Because of this, reduction of nitrophenols has a significant role in the development of modern industries. With this basis, applicability of the titled sample as catalyst for the reduction of nitroaromatics such as nitrophenols (ortho-, meta-, and para-), nitroaniline (ortho-, meta-, and para-) was examined.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The applicability of these three samples for the oxidative decolorization of dye molecules, MO and XO has been examined. As the absorbance maxima of MO and XO occurred at 500 and 430 nm, respectively, progress of the reaction was monitored by measuring the absorbance maxima with time. From the results shown in Figures and , it was found that nearly 89 and 88% of MO and XO were decolorized in 30 and 20 min, respectively, employing Th 0.50 Bi 0.50 O 2−δ sample prepared from solution combustion synthesis. The pseudo first-order rate constants extracted for these heterogeneous reactions were 0.0701 min –1 (for MO) and 0.0642 min –1 (for XO).…”
Section: Resultsmentioning
confidence: 99%